Uji Efektivitas Fungisida Alami dan Sintetis dalam Mengendalikan Penyakit Layu Fusarium pada Tanaman Tomat yang Disebabkan oleh Fusarium oxysporum f.sp. lycopersici - APRIANI, LASTRI; SUPRAPTA, DEWA NGURAH; TEMAJA, I GEDE RAI MAYA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.3, No.3, Juli 2014, 2014)
ABSTRACT The Test of Natural and Synthetic Fungicides Effectiveness in Controlling Fusarium Wilt of Tomato Plants Caused by Fusarium oxysporum f.sp. lycopersici Fusarium wilt caused by Fusarium oxysporum f.sp. lycopersici is one of important diseases in tomato plants. The emersion of the disease can result in huge loss for farmers. The use of synthetic fungicides that has been widely utilized all this time by farmers to control diseases caused by Fusarium oxysporum f.sp. lycopersici has adverse environmental impacts, therefore it is required biological fungicide that is more environmentally friendly. This study is purposed to testing the effectiveness of some natural fungicides and synthetic fungicide, is like a betel leaf, Trichoderma harzianum fungus, Klebsiella pneumoniae , and benomyl for suppress F. oxysporum f.sp. lycopersici and restrained Fusarium wilt diseases . The result of this study shows that the biological fungicide of betel leaf extract can inhibit the pathogenic F. oxysporum f.sp . lycopersici by 76.11 % and the percentage of inhibition potency of other benomyl fungicides reaches 61.11 % , while Klebsiella pneumoniae is by 54.42 % , and 20.98 % for Trichoderma harzianum on PDA medium. The result of field test shows that the extract of betel leaf can suppress Fusarium wilt by 5 % , T. harzianum , benomyl and K. pneumoniae are able to suppress Fusarium wilt respectively by 2.5 %. The use of T. harzianum and K. pneumoniae as biological control has the same effectiveness with synthetic fungicide in order to suppress Fusarium wilt.   Keywords: fusarium wilt, fusarium oxysporum f.sp. lycopersici, biological fungicide